First‐in‐Human Case Study: Multipotent Adult Progenitor Cells for Immunomodulation After Liver Transplantation. (3rd June 2015) - Soeder, Yorick; Loss, Martin; Johnson, Christian L.; Hutchinson, James A.; Haarer, Jan; Ahrens, Norbert; Offner, Robert; Deans, Robert J.; Van Bokkelen, Gil; Geissler, Edward K.; Schlitt, Hans J.; Dahlke, Marc H.
Abstract : Mesenchymal stem cells and multipotent adult progenitor cells (MAPCs) have been proposed as novel therapeutics for solid organ transplant recipients with the aim of reducing exposure to pharmacological immunosuppression and its side effects. In the present study, we describe the clinical course of the first patient of the phase I, dose‐escalation safety and feasibility study, MiSOT‐I (Mesenchymal Stem Cells in Solid Organ Transplantation Phase I). After receiving a living‐related liver graft, the patient was given one intraportal injection and one intravenous infusion of third‐party MAPC in a low‐dose pharmacological immunosuppressive background. Cell administration was found to be technically feasible; importantly, we found no evidence of acute toxicity associated with MAPC infusions. Significance: Liver transplantation is the only definitive treatment for liver failure. However, in order to prevent rejection of the graft, patients must receive lifelong pharmacological immunosuppression, which itself causes clinically significant side effects. This study provides preclinical evidence that mesenchymal stem cells (MSCs) and multipotent adult progenitor cells (MAPCs) can prolong allogeneic solid organ transplant survival in animals by switching the host response toward operational tolerance. To examine the safety and feasibility of MAPC therapy in patients receiving a living‐related or dead‐before‐donation unrelated donor liver graft, the MiSOT‐I (Mesenchymal Stem Cells in Solid Organ Transplantation Phase I) trial was designed. The first study patient, a 27‐year‐old male with liver cirrhosis of unknown etiology, received a living‐related adult right liver graft from his brother. MAPC administration in both the operating room (day 0) and intensive care unit (day 2) was feasible, and no evidence was seen of acute complications associated with the cell infusion. The absence of any acute clinical complications of cell infusion is reassuring for the future administration of MAPCs.